Bank Attributes and Demographic Factors In Determining Customer Choice In Retail Banking: An Analytical Hierarchy Approach - Muhamad Jantan,; Abdul Razak Kamaruddin,; Ong Bian Hoe, (Asian Academy of Management Journal, 1998)
Bank Attributes and Demographic Factors In Determining Customer Choice In Retail Banking: An Analytical Hierarchy Approach(PDF not available)